Raluca Bianca Roman, Sofiya Zahova, Aleksandar Marinov (eds.): Roma Writings: Romani Literature and Press in Central, South-Eastern and Eastern Europe from the 19th Century until World War II: Paderborn: Brill, 2021, 276 s., ISBN 978-3-506-70520-4 - Dunajeva, Jekatyerina (Romano džaniben, 2022)
RECENZE